New approach of hidden data in the portable executable file without change the size of carrier file using statistical technique - Naji, Ahmed Wathik; Gunawan, Teddy Surya; Zaidan, A.A.; O-Khalifa, Othman; Zaidan, B.B.; Al-Khateeb, Wajdi Fawzi Mohammed; Hameed, Shihab A. (IJCSNS, 2009)
The rapid development of multimedia and internet allows for wide distribution of digital media data. It becomes much easier to edit, modify and duplicate digital information. In additional, digital document is also easy to copy and distribute, therefore it may face many threats. It became necessary to find an appropriate protection due to the significance, accuracy and sensitivity of the information. The strength of the hiding science is due to the non-existence of standard algorithms to be used in hiding secret messages. Also there is randomness in hiding methods such as combining several media (covers) with different methods to pass a secret message. Furthermore, there is no formal method to be followed to discover a hidden data. In this paper, a new information hiding system is presented. The aim of the proposed system is to hide information (data file) in an execution file (EXE) without change the size of execution file. The new proposed system is able to embed information in an execution file without change the size of execution file. Meanwhile, since the cover file might be used to identify hiding information, the proposed system considers overcoming this dilemma by using the execution file as a cover file.